Juridical Review of Provisions on Time Limits for Investigations for General Criminal Actions Regarding the Protection of the Rights of Suspects - Muhammad Zulfan Fathur Rohman; Candra Lesmana; Ruslan Baidhowi Kamal; Agus Dimyati (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The phenomenon of criminal law enforcement today is increasingly losing its direction and is even considered to have reached its lowest point, the justice-seeking community complains about the process of investigating criminal acts (general) which is a convoluted process, protracted and even has no end to its resolution, this situation clearly does not provide legal certainty, justice and benefits in law enforcement, moreover there will be violations of the rights of suspects, one of the causes of this situation is the absence of a provision for the time limit of investigation (vacuum of norms). The research method used in this study is to use the type of Normative legal research with the approach used in this study is a statute approach and a conceptual approach, with the specification of the research is descriptive analytical, while the technique of collecting legal materials used in this study is to use document studies. i.e. documents obtained from the Jatanras Unit of the Source Police Station. Based on the results of the study, it shows that there are no provisions governing the time limit for investigation of suspects from the start of investigation to the transfer of cases to trial, so the status of suspects depends on the investigation process. The absence of a time limit in determining suspects causes legal uncertainty guaranteed in Articles 28D and 281 paragraph (2) of the 1945 Constitution, therefore in the Draft Criminal Procedure Code there is a time limit for investigation as stipulated in article 48 of the Criminal Procedure Bill. Paragraph (1) and Paragraph (3).